High intensity ultrasound effects on heat-induced whey protein isolate gels depend on α-lactalbumin: β-lactoglobulin ratio. (May 2016) - Frydenberg, Rikke P.; Hammershøj, Marianne; Andersen, Ulf; Wiking, Lars
Abstract: The effects of high intensity ultrasound (HIU) treatment on physical properties of whey protein isolate (WPI) gels, i.e., water holding capacity, gel strength and elasticity, were studied. WPIs with different α-lactalbumin:β-lactoglobulin (α-la:β-lg) ratios were subjected to ultrasonication (24 kHz, 300 W cm −2, 2078 J mL −1 ) with and without temperature control, i.e., T < 20 °C and T < 65 °C, respectively. Effects of ultrasonication were greatly affected by the relative amount of α-la, most likely due to the type of interactions formed during gelation after ultrasonication. For WPI with relative high α-la content ultrasonication improved the water holding capacity and gel strength of the heat-induced gels. To the contrary, for WPIs with intermediate or low α-la content, no changes in physical properties were observed. These results contribute to clarifying the mechanisms underlying the effects of HIU on WPI, linking effects on protein level to physical properties.